On the 70th anniversary of the Scientific and Experimental station "Otradnoe" of the Komarov Botanical Institute RAS - Latmanizova Tatiyana Mikhailovna (Hortus Botanicus, 2017)
In 2016 was 70 anniversary of Research and Experimental Station "Otradnoe" of the Komarov Botanical Institute. The idea of the collection and publication of the bibliography of works written on the basis of research conducted and conducted on the scientific and experimental station of the Komarov Botanical Institute, Academy of Sciences of the USSR (1946-1991) and the Russian Academy of Sciences (since 1992) came to the 60-th anniversary of the station. For nearly 5 years (from 2001 to 2006.) The author collected data on all publications of the Institute employees, post-graduate students in different years worked in "It is gratifying" and write an article based on materials collected at the station. During this time, were collected the bibliography for nearly 650 publications. At the station were carried out research on the various sections of botany: developmental biology (ontogeny, antecology), anatomy and morphology, geobotany (grassland ecology, soil science), on the introduction of wild trees and shrubs, herbaceous, ornamental, medicinal, attar and other useful plants, productivity and the accumulation of biologically active substances, plant physiology, mycology. This station is located on the Karelian Isthmus in Priozersk district of Leningrad region (60°50' N and 30°15' W), 7 km from the "Otradnoe" railway station, 3 km from the village of "Plodovoye" and 25 km from the town of Priozersk and 100 kilometers from St. Petersburg. It is located 12 km west of Lake Ladoga, on the southwestern tip of the peninsula, jutting deep into the lake Otradnoye (former local name is Pyuhi-Jarvi). Now the station has the status of protected area.